Dari Islamisasi Ilmu Menuju Pengilmuan Islam: Melawan Hegemoni Epistemologi Barat - Ismail Ismail; Mukhlis Mukhlis (Universitas Islam Negeri Mataram, 2013)
Islamization project as epistemological means of knowledge by Ismail R. al-Faruqi, focuses on Islamic disengagement spirit to pursue its science and technology backwardness. This research aims at analyzing the concept weaknesses and improves them. Methods employed are analyzing basic elements and characteristics of knowledge of which the Islamic label is considered inappropriate. The research findings suggest that the formulation of scientific Islam is considered more appropriate as this is where Islamic values become ethics not because of its Islamic label but its own value goodness.